PENGARUH TERAPI MUSIK KLASIK TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN LUKA KAKI DIABETES MELITUS TIPE II DI ASRI WOUND CARE CENTER MEDAN - Yuni Ramadhani; Fitri Yanti Bangun; Verany Melinda Purba; Nazira Addini Batubara (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2025)
Type II Diabetes Mellitus is a chronic metabolic disorder caused by the body's inability to effectively regulate blood sugar levels due to insulin, which increases blood sugar concentrations (hyperglycemia). Classical music therapy provides a relaxing effect that can lower blood sugar levels. The purpose of this study was to identify the effect of classical music therapy on reducing blood sugar levels in patients with type II diabetic foot ulcers at the Asri Wound Care Center in Medan. This study used a quasi-experimental method with a pretest-posttest control group design. The study was conducted at the Asri Wound Care Center in Medan. A sample of 40 respondents was recruited using a purposive sampling technique. The measuring instrument used was an Easy Touch Glucose, Cholesterol, and Uric Acid (GCU) glucometer The results of the independent t-test showed a p-value of 0.000. Because the p-value was less than 0.05, it can be concluded that classical music therapy has a significant effect on reducing blood sugar levels. This can be proven by the pretest and posttest results, which showed significant improvements. This research is expected to provide useful information for improving the quality of education